Harmonisasi Tradisi Pesantren dan Kurikulum Formal Integrasi Pembelajaran Mulok Hadits Salaf di MA Al Anwar Sarang - Anggie Eka Cahyani; Rifaatin Aditiya Cahyani (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
This article discusses the harmonization between pesantren (Islamic boarding school) traditions and the formal curriculum through the integration of the local content subject Hadith Salaf at MA Al Anwar Sarang, Rembang. This study was motivated by the need for Islamic educational institutions to preserve traditional pesantren values amid modernization and the demands of the national curriculum. Data were obtained through in depth interviews with the curriculum coordinator and the Hadith Salaf teacher, and analyzed using a qualitative descriptive approach. The findings show that curriculum integration is carried out through regular coordination among teachers, adjustment of Core Competencies (KI) and Basic Competencies (KD), and the development of contextual learning modules. The Hadith Salaf subject at MA Al Anwar emphasizes not only cognitive understanding but also character formation and students’ moral development. Learning methods such as sorogan, nadhoman, discussion, and storytelling are used to convey hadith values interactively. Meanwhile, the use of digital media such as PowerPoint demonstrates the school’s adaptation to educational technology. This integration has a significant impact on students learning motivation, discipline, and politeness. The integrative model implemented at MA Al Anwar proves that pesantren can transform without losing their identity, serving as a concrete example of Islamic education that is harmonious, adaptive, and relevant to the needs of modern times.